Exploring interactive and interactional metadiscourse in expository writings of ESL hard science and soft learners/ Masliza Mat Zali ... [et al.] - Mat Zali, Masliza; Abdul Rahman, Nurul Ajleaa; Setia, Roszainora; ., Ana (Universiti Teknologi MARA, Sabah, 2024)
The coherence of an essay is maintained with interactive and interactional metadiscourse (MD). Writing involves one-way interaction between the writer and reader, making it difficult for Second Language (L2) learners to compose effectively and thoroughly. Furthermore, students have a limited understanding of MD markers and prefer to exclusively employ specific MD markers, such as transition markers and self-mentions, in their writing. The study aims to find out if learners in different course groups employ different MD types, different MD features, or the same amount of MD features across the two groups. This study evaluates interactive and interactional MD markers in 40 expository essays authored by ESL learners from hard and soft science courses using Hyland's MD table (2005). Data collected was charted and transferred into frequency and percentage. The two groups, hard science and soft science used different materials in varying amounts and varieties. Soft science learners generated more MD features for interactive and interactional MD. They were more interpretative, whereas hard science learners were assertive in their writing and produced fewer MD features for both MD types. The study provides insight into improving students' awareness and use of MD, thereby enhancing their writing performance.